Age-dependent elastin degradation is enhanced in chronic obstructive pulmonary disease. Issue 4 (1st September 2016) - Huang, Jeffrey T.J.; Bolton, Charlotte E.; Miller, Bruce E.; Tal-Singer, Ruth; Rabinovich, Roberto A.; Palmer, Colin N.A.; Thomson, Neil C.; MacNee, William
Chronic obstructive pulmonary disease (COPD) is primarily a lung condition characterised by the presence of persistent airflow limitation resulting from inflammation, remodelling of small airways, and emphysema. It is well-recognised that the impacts of COPD extend beyond the lung with many patients suffering systemic manifestations such as cardiovascular diseases that affect morbidity and mortality [1]. "Accelerated ageing" has been proposed as a mechanism that underlies many of the pulmonary and extrapulmonary consequences of COPD [2, 3]. It is thought that a decline in organ function is a feature of ageing in response to the accumulation of cell and molecular damage, and in the case of COPD, noxious inhalants such as tobacco smoke increase this damage, thus accelerating the ageing process, leading to the development of COPD. With the exception of lung function decline, however, evidence indicating that tobacco smoking or COPD accelerates age-associated deterioration remains scarce. Elastin turnover increases with chronological age and COPD accelerates this process beyond normal ageing http://ow.ly/7OhE301B9z9